The Legacy of Islamic Civilization During the Reign of Caliph Harun al-Rashid - Ardiansyah, Moch. Farrell; Ramadhan, Fazar; Naja, M.Luthfi Robihun; Maulana, Akhmad Nur (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine Islamic civilization during the caliphate of Harun al-Rashid (170–193 AH / 786–809 CE). The main focus of the research is to understand the developments in education, politics, society, economy, and culture that took place during Harun al-Rashid's reign, as well as their influence on the advancement of Islamic civilization. The research employs a library research method, using historical books, journal articles, and relevant documents, with content analysis as the approach.The findings of this study indicate that the caliphate of Harun al-Rashid was a pivotal period in the development of Islamic civilization. In the field of education, Harun al-Rashid successfully established the "Bayt al-Hikmah" (House of Wisdom), which became an iconic symbol of the Islamic Golden Age during the Abbasid period. This library not only symbolized civilization but also became a center of enlightenment for the Islamic world and influenced Western civilization. It served as a hub for the translation and transcription of intellectual works from countries such as Persia and ancient Greece.This demonstrates that Harun al-Rashid’s educational initiatives were successful in advancing Islamic knowledge. Furthermore, the progress in scientific understanding contributed to significant economic growth during his time. This study is important to explore, as it reveals the remarkable intellectual vision of the great Caliph Harun al-Rashid.